DEIXIS IN THE LEGEND OF LAKE TOBA STORY - Gina Lugina; Eka Nuryulia R; Dasep Suprijadi (IKIP Siliwangi, 2019)
Language is more than a sign as it can function as a tool for communication among humans. This means that language can be learned by the humans. One of the fields that study the language is pragmatics. Pragmatics can be defined as the study of contextual meaning; therefore there should be a relationship between language and the context. However, this relationship can be recognized through deixis. The purpose of this paper is to analyze the types of deixis found in the story of “The Legend of Lake Toba”. This paper uses descriptive qualitative method, because it analyzes the types of deixis found in the story. The method of collecting the data is documentation. Specifically using theory of Alan Cruse (2000) about deixis. The steps to analyze the data are reading the story, finding the deixis, and classifying the types of deixis. The finding showed that the types of deixis like personal deixis, spatial deixis, and temporal deixis are used in The Legend of Lake Toba story. In this research, personal types is the dominant types that occur in this story.